Reflexion and control mathematical models - Novikov, D. A. (Dmitriĭ Aleksandrovich) 1970-; Chkhartishvili, A. G. (Aleksandr Gedevanovich) (Communications in cybernetics, systems science and engineering, 2014)
The book considers the basics of mathematical modeling of reflexive processes in control. The models of informational and strategic reflexion allow describing and studying the behavior of reflexing subjects, investigating the relationship between payoffs gained by agents and their reflexion ranks, solving problems of informational and reflexive control in organizational, economic, social and other systems, and military applications among others (the book contains over 30 examples of possible applications in these fields), describing uniformly many phenomena connected with reflexion, viz., implicit control, informational control via the mass media and reflexion in psychology